The segmentation of the labour market of higher education graduates in Portugal - Suleman, F.; Figueiredo, M. C. T.; Suleman, A. (International Conference Democracy and Participation in the 21st Century, 2017)
This study reassesses the segmentation arguments in the context of higher education (HE) graduates. Available literature suggests that investments in human capital seem to be insufficient to facilitate the transition from school to work and less again to good jobs. This subject becomes more pronounced in Portugal where considerable investments in HE have taken place in last decades. Using Labour Force Survey data for 2014 and a fuzzy cluster analysis, we attempt to identify the segments of jobs assigned to HE graduates. Although the dualism was found in HE labour market, the combination of characteristics gives rise to multiple typologies. We found a segment of part-time workers with an employment contract with temporary agencies. The graduates in this cluster have lower wages, are multiple job holders and have shift work; they often work on week-end, in evening and nights. This is particularly the case of fresh graduates from health and services fields of education; who had a spell of unemployment; and are now employed in sales and health sectors. Another segment shows similarities with this cluster but graduates have full-time contracts and the highest wages. However, multiple jobs are also an important characteristic of this cluster. These graduates are from mathematics, engineering, and IT and work in sectors like information and communication, consultancy, and education. Often, they work at home. A third segment balances with these two clusters, and shows graduates in full-time and standard work with medium wages. Here, the graduates predominately perform financial activities, consultancy and manufacturing. The results evidence a segmented labour market of graduates in Portugal, although flexible (stable) employment contracts appear to be no distinctive feature of such segmentation.